2022
DOI: 10.1136/jnis-2022-019246
|View full text |Cite
|
Sign up to set email alerts
|

Impact of aspiration catheter size on clinical outcomes in aspiration thrombectomy

Abstract: BackgroundDirect aspiration thrombectomy is a well-established method for mechanical thrombectomy in acute ischemic stroke. Yet, the influence of aspiration catheter internal diameter (ID) on aspiration thrombectomy efficacy is incompletely understood.MethodsA systematic literature review and meta-regression analysis was completed to evaluate the impact of primary aspiration thrombectomy outcomes based on the ID of the aspiration catheter. Primary outcome measures were: final recanalization of modified Thrombo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…The evolution of EVT devices, including the use of BGC and more complex SR designs, certainly led to improved recanalization rates, but it appears that it was principally the use of larger diameter aspiration catheters that drove the improvement of recanalization results during the study period. 38 Based on a description of EVT outcomes in a large multicenter national registry, our study provides reliable and detailed endpoints for EVT result assessments over time. Indeed, efforts should focus on the rate of FPE for which there is still room for improvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The evolution of EVT devices, including the use of BGC and more complex SR designs, certainly led to improved recanalization rates, but it appears that it was principally the use of larger diameter aspiration catheters that drove the improvement of recanalization results during the study period. 38 Based on a description of EVT outcomes in a large multicenter national registry, our study provides reliable and detailed endpoints for EVT result assessments over time. Indeed, efforts should focus on the rate of FPE for which there is still room for improvement.…”
Section: Discussionmentioning
confidence: 99%
“…The evolution of EVT devices, including the use of BGC and more complex SR designs, certainly led to improved recanalization rates, but it appears that it was principally the use of larger diameter aspiration catheters that drove the improvement of recanalization results during the study period. 38…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the authors found a higher rate of symptomatic hemorrhages with larger bore catheters. 21 Patients enrolled in the DA arm of the ASSIST Registry did not have a significant difference in first pass reperfusion with larger bore catheters compared with smaller bore catheters.…”
Section: Ischemic Strokementioning
confidence: 92%